PENGEMBANGAN FLIPBOOK DALAM PENGUATAN LITERASI DIGITAL PADA MATERI IPS KELAS VII MTs - Maharani, Silfi Ajeng; Pebri Setiani, Puspita (Jurnal Muara Pendidikan, 2024)
The limited understanding of students in studying social studies causes very minimal learning media used by teachers. This leads to students becoming disinterested and failing to grasp the content during the learning process. The objective of this study is to enhance the digital literacy of students at Mts. The developed flipbook learning tool is designed for seventh-grade social studies, focusing on the introduction of Hinduism and Buddhism into Indonesia. This research adopts the Research and Development (R&D) approach, encompassing five stages: 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. Data collection involved questionnaire assessments conducted by media and subject matter experts, along with small-scale group trials at MTS Mafatihul Huda in Madiredo village, Pujon subdistrict. The outcome of this development effort is a digital flipbook learning tool tailored for studying the entry of Hinduism and Buddhism into Indonesia within the social studies curriculum. The findings from the validation research by media experts indicated a feasibility rate of 79%, deemed acceptable. Similarly, material experts assessed the media with a 96% feasibility rate, considering it highly suitable. During small group testing, student assessments yielded a 94% feasibility rate, affirming the media's strong suitability. Consequently, based on these outcomes regarding the digital flipbook media used in teaching Social Sciences, specifically on the topic of The Entry of Hinduism and Buddhism to Indonesia in class VII, it is evident that the material is highly appropriate for application as a learning tool.